2018
DOI: 10.1016/j.foodres.2017.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sweetness preference in red wine according to consumer characterisation

Abstract: The preference for sweet taste in red wine was examined according to consumer categories of age, gender, drinking experience and personality type (Big-5 personality-test). A total of 114 subjects revealed their preferences for sweetness after tasting dry red wine spiked with equal concentrations of glucose and fructose at 2g/L, 4g/L, 8g/L, 16g/L and 32g/L, following an ascending forced choice paired comparison method (2-AFC). The overall preference for sweetness was shown within the range of 4.8 to 21.9g/L, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Item 8 (When I think of something tasty, like a chocolate chip cookie, I have to have one) is related to the pleasure feelings responding to the sweets. Women with higher scores on item 8 in present study might be consistent with the previous findings that women appreciated sweetness more than males did (Katou et al, 2005; Sena-Esteves et al, 2018). Notably, no studies have examined the measurement invariance of the TEPS across gender in other cultural contexts, so it is not clear whether the non-invariant intercepts of item 4 and 8 exist only in Chinese male and female, which warrants future exploration.…”
Section: Discussionsupporting
confidence: 93%
“…Item 8 (When I think of something tasty, like a chocolate chip cookie, I have to have one) is related to the pleasure feelings responding to the sweets. Women with higher scores on item 8 in present study might be consistent with the previous findings that women appreciated sweetness more than males did (Katou et al, 2005; Sena-Esteves et al, 2018). Notably, no studies have examined the measurement invariance of the TEPS across gender in other cultural contexts, so it is not clear whether the non-invariant intercepts of item 4 and 8 exist only in Chinese male and female, which warrants future exploration.…”
Section: Discussionsupporting
confidence: 93%
“…Kampov-Polevov et al [88] reported an association between sweetness preference (of the strongest sucrose solution) and either mood or uncontrolled eating habits. Sweetness preference was associated with many different personality traits, including having greater impulsiveness or lower openness [89], being a novice alcohol-drinker or less extroverted [90], having greater choice impulsivity [91], and being highly outgoing or having a low or medium type A personality [92]. Together, the limited evidence is highly heterogeneous when attempting to assess the effects of various personality traits on sweetness preference, with no clear or consistent associations.…”
Section: Personality Traits and Sweetness Preferencementioning
confidence: 99%
“…taste recognition and valence), however, is cognitive processing of the inputs coming to the brain from the physiological reaction to the chemical substance. This cognitive processing is made according to taste patterns stored in the individual’s memory (Sena-Esteves et al , 2018). These patterns are accumulated and developed through the taste experiences the individual had in his/her life (Rosch, 1988).…”
Section: Odor-taste Interactionmentioning
confidence: 99%
“…The results show that female participants had higher ratings for food pungency, which affected their food liking of spicy food. Laaksonen et al (2016) and Sena-Esteves et al (2018) found that female participants preferred sweeter samples of solid and liquid food when compared to male participants.…”
Section: Gender Differences In Odor-taste Interaction and Subsequent Healthy Food Choicesmentioning
confidence: 99%